2014
DOI: 10.1055/s-0033-1363224
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Changes in Adiposity Distribution on Insulin Resistance and Adiponectin Variations Over 4 Years in Normal Weight Young Adults

Abstract: The aim of the study was to evaluate the influence of weight gain and changes in adiposity distribution on insulin resistance and circulating adiponectin variations over 4 years in free-living normal weight young adults. In this prospective observational cohort (n=42 women, 18 men), anthropometric measurements and blood samples were collected in the fasting state at baseline and at 4 years. Insulin resistance was estimated using the homeostatic model assessment (HOMA-IR). Circulating adiponectin levels were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…As reported in our study, physical activity was positively associated with log HOMA2-B in both age groups, therefore, lifestyle modification such as physical activities or reducing weight gain bring benefit to preserve β-cell function in individuals with prediabetes [32]. Drug such as vildagliptin may also help to repair impairments in pancreatic β-cell function and insulin resistance [33].…”
Section: Discussionsupporting
confidence: 61%
“…As reported in our study, physical activity was positively associated with log HOMA2-B in both age groups, therefore, lifestyle modification such as physical activities or reducing weight gain bring benefit to preserve β-cell function in individuals with prediabetes [32]. Drug such as vildagliptin may also help to repair impairments in pancreatic β-cell function and insulin resistance [33].…”
Section: Discussionsupporting
confidence: 61%
“…The link between FAI, IR and adiponectin levels may exist for several reasons. Prospective studies have shown a relationship between IR and decreased adiponectin levels with weight gain and increased waist circum ference [39]. Furthermore, since androgens promote central adi posity and visceral adipose deposition, differences in adipose tissue distribution may influence the secretion of the different adipocytokines and pro-inflammatory proteins, such as TNF-α and IL6, which are upregulated in PCOS patients [40]; these cytokines may downregulate the expression of adiponectin.…”
mentioning
confidence: 99%
“…Adipose tissue quantity, as measured with either BMI or waist circumference (WC) is related to plasma concentrations of adipokines, to morphologic characteristics of adipose tissue, and to the development of the metabolic syndrome, DM2, and vascular diseases [39][40][41]. Pro-inflammatory adipokines (IL-6, IL-8, IL-18, TNF-α, PAI1, and leptin) are known to be positively correlated with both BMI and WC [42][43][44][45], whereas the anti-inflammatory adiponectin is negatively correlated with BMI and WC [42][43][44][45][46]. In subcutaneous adipose tissue biopsies, IL-6 and IL-8 expression are associated with waist circumference [47].…”
mentioning
confidence: 99%